UTERINE ADENOMATA IN THE RABBIT : III. SUSCEPTIBILITY AS A FUNCTION OF CONSTITUTIONAL FACTORS - Greene, Harry S. N. (The Rockefeller University Press, 1941)
An investigation of uterine adenomata in the rabbit revealed an incidence of 16.7 per cent in the total female population over 2 years of age. However, the incidence varied widely in relation to age, breed, and genetic constitution and closely paralleled that of toxemia of pregnancy with reference to the same constitutional factors. In addition, all of the tumor bearing animals suffered attacks of this disease during their earlier breeding history. The facts suggest that the association of the two disorders occurred as a result of the liver damage incident to toxemia which impaired the function of this organ in relation to estrin inactivation and the concentration of this substance in the blood stream subsequently rose to a carcinogenic level. A consideration of the disparity in the distribution of uterine growths in rabbits and women indicated that the absence of squamous epithelium in the cervix of the rabbit and the greater physiological activity of the endometrium of the fundus in this species were the determining factors.